2008
DOI: 10.4049/jimmunol.180.8.5163
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Broad Expression of the FoxP3 Locus in Epithelial Cells: A Caution against Early Interpretation of Fatal Inflammatory Diseases following In Vivo Depletion of FoxP3-Expressing Cells

Abstract: Dogma that the regulatory T cell (Treg) prevents catastrophic autoimmunity throughout the lifespan relies on the assumption that the FoxP3 locus is transcribed exclusively in Treg. To test the assumption, we used the Rag2−/− and the Rag2−/− mice with the Scurfy (sf) mutation (FoxP3sf/Y or FoxP3sf/sf) to evaluate FoxP3 expression outside of the lymphoid system. Immunohistochemistry and real-time PCR revealed FoxP3 expression in breast epithelial cells, lung respiratory epithelial cells, and prostate epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 17 publications
4
106
3
1
Order By: Relevance
“…More recently, in support of the notion of essential role for Treg throughout the lifespan, it was reported that deletion of FoxP3-expressing cells cause acute lethal inflammation in the immune competent adult mice (22), although this finding has been disputed by another group (23). However, given our observation of FoxP3 expression in epithelial cells in mammary gland, thymus (24,25), and lung (26), it is unclear whether the cellular ablation is restricted to the Treg lineage. Expression of the FoxP3 gene in lung epithelial cells may well contribute to the lethal inflammation when high doses of diphtheria toxin was used to treat the mice in which the diphtheria toxin receptor were knocked into the FoxP3 locus.…”
Section: Homeostatic Proliferation In the Mice With Germlinecontrasting
confidence: 43%
“…More recently, in support of the notion of essential role for Treg throughout the lifespan, it was reported that deletion of FoxP3-expressing cells cause acute lethal inflammation in the immune competent adult mice (22), although this finding has been disputed by another group (23). However, given our observation of FoxP3 expression in epithelial cells in mammary gland, thymus (24,25), and lung (26), it is unclear whether the cellular ablation is restricted to the Treg lineage. Expression of the FoxP3 gene in lung epithelial cells may well contribute to the lethal inflammation when high doses of diphtheria toxin was used to treat the mice in which the diphtheria toxin receptor were knocked into the FoxP3 locus.…”
Section: Homeostatic Proliferation In the Mice With Germlinecontrasting
confidence: 43%
“…Foxp3 expression in noncancerous epithelial cells was investigated in Rag2 À/À mice, which are notably devoid of T lymphocytes, and in mice with the Scurfy mutation that deletes Foxp3 expression (Chen et al, 2008). This study revealed expression of Foxp3 mRNA and protein in the nuclei of epithelial cells in the breast, lung and prostate, but not in the liver, kidney and intestine.…”
Section: Foxp3 Expression In Normal and Cancerous Human Cellsmentioning
confidence: 98%
“…Treg are a rare subset of T cells responsible for preventing inappropriate immune responses and promoting immune tolerance (Fontenot et al, 2003;Marson et al, 2007;Feuerer et al, 2009;Josefowicz and Rudensky, 2009). Although originally thought to be T-cell-restricted, FOXP3 expression appears widespread in normal epithelia and aberrant in solid tumours, suggesting that FOXP3 can function as a tumour suppressor (Chen et al, 2008;Martin et al, 2010;Ladoire et al, 2011). As evidence, female heterozygous, Foxp3-knockout mice have a significant age-dependent increase in spontaneous mammary cancer.…”
Section: Introductionmentioning
confidence: 99%